2x+3x(x-5)=130

Simple and best practice solution for 2x+3x(x-5)=130 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3x(x-5)=130 equation:


Simplifying
2x + 3x(x + -5) = 130

Reorder the terms:
2x + 3x(-5 + x) = 130
2x + (-5 * 3x + x * 3x) = 130
2x + (-15x + 3x2) = 130

Combine like terms: 2x + -15x = -13x
-13x + 3x2 = 130

Solving
-13x + 3x2 = 130

Solving for variable 'x'.

Reorder the terms:
-130 + -13x + 3x2 = 130 + -130

Combine like terms: 130 + -130 = 0
-130 + -13x + 3x2 = 0

Begin completing the square.  Divide all terms by
3 the coefficient of the squared term: 

Divide each side by '3'.
-43.33333333 + -4.333333333x + x2 = 0

Move the constant term to the right:

Add '43.33333333' to each side of the equation.
-43.33333333 + -4.333333333x + 43.33333333 + x2 = 0 + 43.33333333

Reorder the terms:
-43.33333333 + 43.33333333 + -4.333333333x + x2 = 0 + 43.33333333

Combine like terms: -43.33333333 + 43.33333333 = 0.00000000
0.00000000 + -4.333333333x + x2 = 0 + 43.33333333
-4.333333333x + x2 = 0 + 43.33333333

Combine like terms: 0 + 43.33333333 = 43.33333333
-4.333333333x + x2 = 43.33333333

The x term is -4.333333333x.  Take half its coefficient (-2.166666667).
Square it (4.694444446) and add it to both sides.

Add '4.694444446' to each side of the equation.
-4.333333333x + 4.694444446 + x2 = 43.33333333 + 4.694444446

Reorder the terms:
4.694444446 + -4.333333333x + x2 = 43.33333333 + 4.694444446

Combine like terms: 43.33333333 + 4.694444446 = 48.027777776
4.694444446 + -4.333333333x + x2 = 48.027777776

Factor a perfect square on the left side:
(x + -2.166666667)(x + -2.166666667) = 48.027777776

Calculate the square root of the right side: 6.930207629

Break this problem into two subproblems by setting 
(x + -2.166666667) equal to 6.930207629 and -6.930207629.

Subproblem 1

x + -2.166666667 = 6.930207629 Simplifying x + -2.166666667 = 6.930207629 Reorder the terms: -2.166666667 + x = 6.930207629 Solving -2.166666667 + x = 6.930207629 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.166666667' to each side of the equation. -2.166666667 + 2.166666667 + x = 6.930207629 + 2.166666667 Combine like terms: -2.166666667 + 2.166666667 = 0.000000000 0.000000000 + x = 6.930207629 + 2.166666667 x = 6.930207629 + 2.166666667 Combine like terms: 6.930207629 + 2.166666667 = 9.096874296 x = 9.096874296 Simplifying x = 9.096874296

Subproblem 2

x + -2.166666667 = -6.930207629 Simplifying x + -2.166666667 = -6.930207629 Reorder the terms: -2.166666667 + x = -6.930207629 Solving -2.166666667 + x = -6.930207629 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.166666667' to each side of the equation. -2.166666667 + 2.166666667 + x = -6.930207629 + 2.166666667 Combine like terms: -2.166666667 + 2.166666667 = 0.000000000 0.000000000 + x = -6.930207629 + 2.166666667 x = -6.930207629 + 2.166666667 Combine like terms: -6.930207629 + 2.166666667 = -4.763540962 x = -4.763540962 Simplifying x = -4.763540962

Solution

The solution to the problem is based on the solutions from the subproblems. x = {9.096874296, -4.763540962}

 

See similar equations:

| n+-3=9 | | (-1+14x)+(12x+17)=180 | | 7a-3=3a+14 | | 4k^2+40k-10=0 | | 3y=-18 | | a^2+6a+8=0 | | x^2+kx+196=0 | | n-(-2)=9 | | 64x^2-kx+1=0 | | x-6=-1 | | x^2-3x-54=0 | | 7x+14-3x=30 | | 15u^2-14u=49 | | -10x+6=-7+-9 | | 5m-19=m-2 | | 4r^2-169=0 | | 6(3-2x)=54 | | 3n+4.6=21.6 | | y+-3=-2 | | (x^2-4x)+(y^2+12y)=9 | | n^2+3-40=0 | | n^2+3n-40=0 | | 2100+9c=14c | | 2(3x)+1=2x+21 | | b^2+8b+7=0 | | -4(t+6)+-8t-8=16 | | .5+.416d=.916+.7d | | r^2-r-12=0 | | b^2+10b+25=0 | | 18x+3Y=3 | | x+6=-3 | | -9n=-63 | | 4p^2+121=44p | | n^2+5-14=0 | | n^2+2r-48=0 | | 3x=18+5x | | 2y=-20 | | r^2+2r-48=0 | | 7x=-42 | | 24-4t=3t+3 | | 8x+8y=44 | | 16m^2-1=0 | | v^2+20v+100=0 | | 8y=-72 | | 2m+40=7m-5 | | -6n=36 | | 5j-14=-9 | | n-7=-9 | | 2r+3=9 | | n^2+3n-54=0 | | 5m+15=8m-3 | | b^2-19b+90=0 | | 4-2(2x-3)=2(x+11) | | .4y-.2(3-y)=1.8 | | r^2-7r-8=0 | | 18-x=x+4 | | 9(f-8)+5f+40=-16 | | (3x+1)(x+1)=(5x+11)(x-1) | | x^2-15x+50=0 | | n-(-4)=7 | | 3x+8=24 | | n^2-2n-8=0 | | (10-x)-4=1 | | y+7=4 | | 4(2x+1)-7=6-5 |